Effects of microwave pulse-width damage on a bipolar transistor - 马振洋 柴常春 任兴荣 杨银堂 陈斌 赵颖博 (Chinese physics B, 2012)
This paper presents a theoretical study of the pulse-width effects on the damage process of a typical bipolar transistor caused by high power microwaves（HPMs） through the injection approach.The dependences of the microwave damage power,P,and the absorbed energy,E,required to cause the device failure on the pulse width τ are obtained in the nanosecond region by utilizing the curve fitting method.A comparison of the microwave pulse damage data and the existing dc pulse damage data for the same transistor is carried out.By means of a two-dimensional simulator,ISE-TCAD,the internal damage processes of the device caused by microwave voltage signals and dc pulse voltage signals are analyzed comparatively.The simulation results suggest that the temperature-rising positions of the device induced by the microwaves in the negative and positive half periods are different,while only one hot spot exists under the injection of dc pulses.The results demonstrate that the microwave damage power threshold and the absorbed energy must exceed the dc pulse power threshold and the absorbed energy,respectively.The dc pulse damage data may be useful as a lower bound for microwave pulse damage data.